COVID-19 briefing. Exploring attitudes and behaviours in England during the COVID-19 pandemic (2020)
To supplement our Active Lives (Adult and Children & Young People) Surveys, we are publishing a series of briefings providing a regular picture of physical activity behaviours and attitudes during the different phases of the COVID-19 pandemic.